Desarrollo de un modelo heurístico para la optimización en el manejo de material en estibas en una bodega (2011)
Warehousing problems have always been characterized depending on the type of businesses that is analyzed. Some businesses have quarantine zones in their warehouses, other don’t have. Some have out-andback picking, others do picking for different items at the same time. Some industries have forward areas, bulk storage areas, retained products areas and rejected products areas. In general, the optimization of warehouses is done depending on all of the characteristics mentioned above. In this research paper, a heuristic has been Desarrollo de un modelo heurístico para la optimización en el manejo de material en estibas en una bodega Diana Ramírez Ríos MSc en Ingeniería Industrial Universidad del Norte, Barranquilla Directora Científica FCIMEC, Fundación Centro de Investigación en Modelación Empresarial del Caribe Barranquilla, Colombia dramirez@fcimec.org Laura Manotas Romero Ingeniería Industrial, Universidad del Norte, Barranquilla Investigador Jr. FCIMEC, Fundación Centro de Investigación en Modelación Empresarial del Caribe Barranquilla, Colombia lpmanotas@fcimec.org adapted from the cube-per-order index rule for slotting optimization merged with some of the picking optimization techniques, where the route distance is important but not the route itself. The application was made to over an warehouse, based on the information provided by a industrial company, where the critical aspect was to know the optimal position of the different areas and the products in the racks that the warehouse have, taking into account the capacities of the racks and the characteristics that certain type of products have. The objective was to minimize the total distance travelled in a specific period of time, taking into account capacity and assignment restrictions. It will be shown the significant improvement in the efficiency of a warehouse of material in pallet, given the application of heuristics developed.